View from the pass: James Whited - Ames, Neil (Raton Range Raton, New Mexico, 1978)
Newspaper Article on families recalling the past. James A. Whited talks of his dad coming to Raton in 1897.
Master list item #: 32
File location is in the Raton File Cabinet
Keywords: Southwell, John; Burch, Tillie; Whited, James A; Whited, James A. Sr; Tadus, Bill; Roosevelt, Theodore; Smithson, James; Cramer, Carl; Lloyd, Betty; Safeway; International Bank; First National Bank; Santa Fe Railroad; Schroeder's; Smithsonian; Kelly Mine; Rocky Mountain Coal Company; Shuler Theater; Arthur Johnson Memorial Library; Local History; Biography; Memories; Jewelry store; Railroad; Coal Mine; Orchestra; Library; Raton, New Mexico; Washington, D.C.; Kelly, New Mexico